Oxidized LDL attenuates apoptosis in monocytic cells by activating ERK signaling - Dmitry Namgaladze; Andreas Kollas; Bernhard Brüne (Journal of Lipid Research, 2008)
Low concentrations of oxidized low density lipoprotein (OxLDL) are cytoprotective for phagocytes, although the underlying mechanisms remain unclear. We investigated signaling pathways used by OxLDL to attenuate apoptosis in monocytic cells. OxLDL at 25–50 μg/ml inhibited staurosporine-induced apoptosis in THP-1 cells and mouse peritoneal macrophages, and it was cytoprotective in human primary monocytes upon serum withdrawal. Attenuated cell demise was reversed by blocking extracellular signal-regulated kinase (ERK) signaling. Translocation of cytochrome c to the cytosol was attenuated by OxLDL, which again demanded ERK signaling. Analysis of Bcl-2 family proteins revealed phosphorylation of Bad at serine 112 as well as ERK-dependent inhibition of Mcl-1 degradation. Although the formation of reactive oxygen species (ROS) is an established signal generated by OxLDL, ROS scavengers did not interfere with cell protection by OxLDL. Thus, activation of the ERK signaling pathway by OxLDL is important to protect phagocytes from apoptosis.